2020
DOI: 10.3389/fmats.2020.00192
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure and Phase Composition of TiO2 P25 Particles After Thermal Treatments and HF Etching

Abstract: The anatase to rutile phase transformation via thermal and chemical (HF etching) routes of TiO 2 P25 has been investigated. The treatment parameters and properties of the resulting anatase and rutile nanoparticles are analyzed and discussed. Since the nature of TiO 2 surfaces plays a significant role in determining the physical and chemical properties of the TiO 2 nanoparticles, it is important to investigate the surface properties, including the morphology, the main exposed faces, the defectiveness, to be cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 67 publications
3
23
0
Order By: Relevance
“…The XRD patterns of pristine catalysts and catalysts with 10 wt.% Ag are shown in Figure 3 . Figure 3 A, corresponding to TiO 2 NWs (pristine or with 10 wt.% Ag), shows intense peaks at 27° (110), 36° (101), and 55° (211), which have been unambiguously ascribed to the rutile phase (JCPDS 88-1175) [ 28 ]. The 10% Ag @ TiO 2 NW diffractogram, as well as the rest of the catalysts with other percentages of silver, showed a small shift towards lower angles compared to the pure TiO 2 NWs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The XRD patterns of pristine catalysts and catalysts with 10 wt.% Ag are shown in Figure 3 . Figure 3 A, corresponding to TiO 2 NWs (pristine or with 10 wt.% Ag), shows intense peaks at 27° (110), 36° (101), and 55° (211), which have been unambiguously ascribed to the rutile phase (JCPDS 88-1175) [ 28 ]. The 10% Ag @ TiO 2 NW diffractogram, as well as the rest of the catalysts with other percentages of silver, showed a small shift towards lower angles compared to the pure TiO 2 NWs.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peaks of anatase (JCPDS 21-1272) can be found at ca. 25° (101), 38° (004), 48° (220), 54° (105), and 55° (211) [ 28 ], while the rutile crystalline phase has its characteristic peaks at ca. 27° (110), 36° (101), 41° (111), and 54° (211) (JCPDS 34-180) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Degussa P25, a commercially available TiO 2 , is one of the most efficient photocatalysts in terms of cost and photocatalytic ability, with a number of works published elsewhere [ 7 , 8 , 9 , 10 , 11 ]. Despite that, these studies reported some issues with this particular photocatalyst, and one of them is the high bandgap energy (~3.2 eV) The high bandgap value limits the light utilization efficiency and reduces the number of electrons that could participate in the redox reaction, which consequently deteriorates the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallinity and structural properties of the synthesized TiOF 2 were characterized using an X-ray diffractometer (XRD, Rikagu, D/Max-2500, Austin, TX, USA) equipped with Cu-Kα radiation at 40 kV and 200 mA. Quantitative analyses of TiOF 2 and anatase TiO 2 were carried out using Spurr and Myers relationship (A (wt.%) = 1/(1 + 1.265 × (I O /I F )) × 100, where I O is the integrated intensity of anatase TiO 2 (101) at 25.3° and I F is the integrated intensity of TiOF 2 (100) at 23.4°) to calculate the phase compositions of the synthesized photocatalyst [ 37 , 38 ]. The average crystal sizes were also calculated using the Scherrer equation (L = 0.90λ/(β − βi) cos θ, where β is the observed FWHM (fulll width at half maximum) and is the calculated instrumental broadening) [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%